Tracked Changes. Fibre optic interconnecting devices and passive components. Basic test and measurement procedures. Tests. Sealing for fibre optic sealed closures and hardened connectors using air pressure Part 2-38, (10th October 2023) - British Standards Institution,
No abstract available